If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5(-2x-7)-x=2(x+2)-8
We move all terms to the left:
-5(-2x-7)-x-(2(x+2)-8)=0
We add all the numbers together, and all the variables
-1x-5(-2x-7)-(2(x+2)-8)=0
We multiply parentheses
-1x+10x-(2(x+2)-8)+35=0
We calculate terms in parentheses: -(2(x+2)-8), so:We add all the numbers together, and all the variables
2(x+2)-8
We multiply parentheses
2x+4-8
We add all the numbers together, and all the variables
2x-4
Back to the equation:
-(2x-4)
9x-(2x-4)+35=0
We get rid of parentheses
9x-2x+4+35=0
We add all the numbers together, and all the variables
7x+39=0
We move all terms containing x to the left, all other terms to the right
7x=-39
x=-39/7
x=-5+4/7
| 126=6x+6(-4+4x) | | -23+7x=37-5x | | -3z+4)=6z-3(3z+2) | | 1/2/2=1/3/x | | 1/8(8t-7)=t+7/16 | | 5.5x+0.56=-65.1 | | a+2=-5+2a | | 2(x+3)-6=5x-1 | | 52x3-10x2-8x=0 | | 3(x^2+-2x)=3x^2+5x+-11 | | 1/2x+2*x=18 | | 6(2x+1)-3(5x+2=0 | | 5+14a=9a−5a= | | 3(x+1)-1=3(x-3) | | 0.50z=4.85 | | (6/7)+(1/8)x=2 | | 9(x/3+1)=6 | | .75(8x-4)=6x+5 | | b=55+(10+7) | | 52-3u=58 | | -6x-2x=-8x | | -3/4(-2x+1)=-3 | | 6/7+1/8x=2 | | 0.12/0.8=0.6/x | | (w-5)^2-27=0 | | |3x-2|-2=0 | | 3x-10=9x-16 | | 4x+2=6×-4 | | 5/2s-s=3+3/2s | | 7+2(m-4)=3;1 | | 1/3(9x+3)=x+1 | | -5x+4-3=x+1 |